Vozes femininas em úrsula, de Maria Firmina dos reis, “uma maranhense” - Pinheiro , Thayara Rodrigues (2016)
This research is an analysis of the role of women manifested through what we call the voices of the female characters in the novel of Ursula maranhense Maria Firmina dos Reis. We focus our analysis on the life and work of the author, the role of women in writing of the nineteenth century innovation that romance brings and the main female characters of the work: Ursula, Susana, Luisa B and Adelaide to show how these characters light up in narrative and manifest, thus tracing an act of transgression, since they lived under the patriarchal system. Women in Ursula beyond the traditional, they are not only representing the social roles of daughter, wife and mother, that is, the roles imposed on them are nothing more than a frame to surround what these women wanted to say about you. The women of the nineteenth century were masters of feelings, emotions, desires and dreams that needed to get out of the dark and male variety, showing to the world. The women's writing in eight is not represented purely as an escape for women who found few professional and social alternatives, but as a form of inclusion in the public space, typically male, subverting dominant values and codes.